Drawing in psychoterapy - Kolwińska, Marta (Studia Psychologica: Theoria et praxis, 2004)
Drawing is of great use in psychotherapy. According to many psychologists drawing can be extremely helpful both in making a diagnosis and conducting therapy. Drawing is a simple method of getting to know the patient. This activity doesn't take much time but it provides important materials for interpretation. Drawing is very helpful in improving communication between people and in strengthening self- respect. This article is about history of drawing and its use in psychotherapy. Valuable information about application of drawing in therapy is included in the text.